ANALYSIS OF REVERBERATION EFFECT ON FORMATION OF SEABED IMAGE IN SYNTHETIC APERTURE SONAR - S. R. Heister; T. T. Tran (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A model of reverberation in the synthetic aperture sonar is considered. A assessment of reverberation effect on quality formation of seabed image in synthetic aperture sonar is performed by mathematical simulation with model of reverberant space.